2009
DOI: 10.1080/13561820802602552
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between pharmacists, physicians and nurse practitioners: A qualitative investigation of working relationships in the inpatient medical setting

Abstract: While collaborative, team-based care has the potential to improve medication use and reduce adverse drug events and cost, less attention is paid to understanding the processes of well functioning teams. This paper presents the findings from key informant interviews and reflective journaling from pharmacists, physicians and nurse practitioners participating in a multicentre, controlled clinical trial of team-based pharmacist care in hospitalized medical patients. A phenomenological approach guided the data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
174
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(188 citation statements)
references
References 46 publications
10
174
1
3
Order By: Relevance
“…[3][4][5] However, there is a paucity of literature describing prescriber perceptions of the benefit of a pharmacist or student pharmacist in similar practice environments. 6 Of those published reports that have attempted to capture the role and contribution of pharmacists or student pharmacists, most have been conducted outside of the United States, potentially limiting the transferability of their results to the US health care system; were not conducted in the internal medicine setting; and/or had small sample sizes. [7][8][9][10][11][12] Despite these limitations, the results of this study are similar to those reported in the literature for practicing pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] However, there is a paucity of literature describing prescriber perceptions of the benefit of a pharmacist or student pharmacist in similar practice environments. 6 Of those published reports that have attempted to capture the role and contribution of pharmacists or student pharmacists, most have been conducted outside of the United States, potentially limiting the transferability of their results to the US health care system; were not conducted in the internal medicine setting; and/or had small sample sizes. [7][8][9][10][11][12] Despite these limitations, the results of this study are similar to those reported in the literature for practicing pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving the integration of a pharmacist into a team with a physician and nurse practitioner reported their experiences and perceptions of the successes and challenges of their collaborative effort, as well as ideas for innovation. 3 The study also shed light on the continuing professional development needs of pharmacists as a result of the broadened/additional patient care skills needed within an interdisciplinary care team.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Integration of pharmacists into the team was felt to have positive patient outcomes by improving team drug-therapy decision-making, continuity of care and patient safety. [4] In order to achieve patients' best outcome, effective communication become one of the powerful skill that must be acquired and mastered by every pharmacist. Through effective communication, pharmacists can provide patients with knowledge on drug therapy and thus, increase their compliance.…”
Section: Introductionmentioning
confidence: 99%